1993
DOI: 10.1542/peds.91.2.445
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Rett Syndrome: A Population-Based Registry

Abstract: The Texas Rett Syndrome Registry maintains the largest population-based registry of cases and potential cases of Rett syndrome in the world. The most precise estimate of the prevalence of Rett syndrome of 1 per 22800 (0.44/10000) females aged 2 through 18 years of age was generated from this Registry. In addition, the first prevalence figures for black and Hispanic female cases were estimated. Registry cases are actively ascertamed from multiple sources. Registry staff identify presumptive cases from review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…To our knowledge, this is one of the first real-world evidence studies examining the epidemiology and journey of patients with RTT using large administrative claims data from the US. A prior study using a population-based registry from Texas estimated a RTT prevalence of 0.44 per 10,000 females aged 2–18 years [ 13 ]; while not directly comparable to our overall prevalence estimates due to the age stratification, our estimates are within range of the registry-based prevalence. However, there is sparse literature evaluating HRU and costs associated with RTT [ 9 ].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…To our knowledge, this is one of the first real-world evidence studies examining the epidemiology and journey of patients with RTT using large administrative claims data from the US. A prior study using a population-based registry from Texas estimated a RTT prevalence of 0.44 per 10,000 females aged 2–18 years [ 13 ]; while not directly comparable to our overall prevalence estimates due to the age stratification, our estimates are within range of the registry-based prevalence. However, there is sparse literature evaluating HRU and costs associated with RTT [ 9 ].…”
Section: Discussioncontrasting
confidence: 80%
“…To our knowledge, this is one of the first real-world evidence studies examining the epidemiology and journey of patients with RTT using large administrative claims data from the US. A prior study using a population-based registry from Texas estimated a RTT prevalence of 0.44 per 10,000 females aged 2-18 years [13]; while not directly comparable to our overall prevalence estimates due to the age stratification, our estimates are within f Identified using CPT codes: 81,302-81,304, 0234U, 81,470, 81,471, 81,479 g MECP2 genetic testing date was based on the medical claim associated with a procedure code for MECP2 genetic testing closest to the index date and including on the index date h Based on the specialty of the provider who rendered the service of medical claims associated with a procedure code for MECP2 genetic testing i Pediatric specialist included child neurology, developmental/behavioral pediatrics, pediatric cardiology, pediatric endocrinology, pediatric gastroenterology, and pediatric radiology j Among patients with multiple types of visits on the same day, inpatient stays were prioritized over all other types of visits, followed by ED visits, OP visits, long-term care/skilled nursing facilities, other places of service, and unknown place of service k Consecutive days of inpatient stays, ED visits, or long-term care visits were considered one visit l Evaluated on each distinct day during the baseline period, not including the index date, among patients with ≥ 1 day of clinical activity prior to the index date (N = 4,399) m Place of service was defined by the place associated with each medical claim for which a patient sought healthcare services n Other places of service included home/hospice, independent laboratory, hospital laboratory services provided to non-patients, ambulance, telehealth, and more o Unknown places of service included medical claims associated with other places of service or unassigned places of service. Procedure codes associated with each medical claim were used to define the type of visit p Therapeutic services visit included physical therapy, hydrotherapy, occupational therapy, speech therapy, and feeding assistance q Defined as any medical claim with a procedure code for medical supplies.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, no studies from the USA were published during the review period (1 January 2000 to 30 June 2021). One study was identified, published in 1993 from a large population-based registry in Texas, in which the prevalence of classic RTT was estimated to be 4.4 per 100,000 females [ 30 ]. This is in line with what has been reported in the studies presented here (5 to 10 cases per 100,000 females).…”
Section: Discussionmentioning
confidence: 99%
“…6 Similar rates of RTT are present in all racial and ethnic groupings. 2,7 RTT does not have a degenerative component. Instead, it is a chronic condition that worsens over time and manifests as a variety of multisystem symptoms.…”
Section: Introductionmentioning
confidence: 93%
“…of 2 and 18 (or 0.44 in 10 000). 2 In France, the prevalence per 10 000 girls was 0.56 3 ; however, in Sweden and Scotland was 0.65, 4,5 and 0.72 in Australia. 6 Similar rates of RTT are present in all racial and ethnic groupings.…”
Section: Introductionmentioning
confidence: 98%